2016
DOI: 10.1080/21645515.2016.1158367
|View full text |Cite
|
Sign up to set email alerts
|

No evidence that HPV vaccination leads to sexual risk compensation

Abstract: Uptake of the HPV vaccine has been lower than the uptake of most other childhood vaccines offered in public programs. Since the HPV vaccine protects against a sexually transmitted virus, one barrier to uptake specific to the HPV vaccine may be the concern that vaccination may encourage risky sexual behaviour. Unanimous findings from recent studies show that HPV vaccination does not lead to sexual risk compensation, which is an important message to parents, clinicians and other decision-makers regarding HPV vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
(19 reference statements)
0
7
0
Order By: Relevance
“…Previous studies suggested that most vaccine recipients understood that the HPV vaccines could not provide them 100% protection against STDs and that behaviors to avoid these risks should be continued. 46 About 30% of the participants perceived some positive outcomes of CAI with men after receiving HPV vaccination, such as it would increase intimacy and trust between sex partners. Such positive outcome expectancies were associated with a higher intention to perform risk compensation behaviors after receiving the HPV vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that most vaccine recipients understood that the HPV vaccines could not provide them 100% protection against STDs and that behaviors to avoid these risks should be continued. 46 About 30% of the participants perceived some positive outcomes of CAI with men after receiving HPV vaccination, such as it would increase intimacy and trust between sex partners. Such positive outcome expectancies were associated with a higher intention to perform risk compensation behaviors after receiving the HPV vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…What the PrEP example shows is nothing new. In the last decades, other prevention tools were all met with caution as they could possibly induce behavioural changes leading to an increased risk and consequently counteract the benefit of the prevention tool in question: the oral contraceptive pill in the 1950s , treatment for syphilis in the 1960s and 1970s , needle exchange programmes for injecting drug users , the morning‐after pill , and more recently HPV vaccination . Although different BI for HIV prevention have shown their effectiveness (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…We excluded papers focusing on medical prevention (e.g., medical treatment of risk factors, such as hypertension), as well as secondary (e.g., prostate or breast cancer screening programmes) or tertiary prevention. Regarding borderline cases, such as vaccinations, which can be regarded as a public health or as a medical prevention effort, we excluded those publications exclusively addressing the iatrogenic effects of vaccines as medical products (e.g., fever, immune reactions), but included those reporting on the AUCs of vaccination programmes beyond adverse drug reactions (53). The full list of inclusion and exclusion criteria is provided in Additional File 2.…”
Section: Identification Of Eligible Publications For "Best Fit" Frame...mentioning
confidence: 99%